Analisis Determinan Pembangunan Ekonomi Inklusif di Provinsi Kalimantan Selatan Menggunakan Pendekatan Panel Vector Error Correction Model (PVECM) - Fidiyaningsih, Yani; Farid, Fuad Muhajirin; Rakhmawati, Yeni (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
The success of economic development is measured by the level of equality and sustainability, particularly through the Inclusive Economic Development Index (IEDI), emphasizing even economic growth for all layers of society. This research analyzes the relationship between IEDI and influencing factors, namely the Human Development Index (HDI), Economic Growth (EG), and Percentage of Poor Population (PPP), using the Panel Vector Error Correction Model (PVECM) approach in South Kalimantan Province from 2011 to 2021. The results indicate that the data is integrated at the same level, and there is a cointegration equation with an optimal lag of 5, implying that the impact of changes in HDI and economic growth on IPEI can affect IPEI up to five periods. PVECM estimates show that HDI and economic growth significantly influence IPEI in the long and short term. In the long run, an increase in HDI and economic growth negatively impacts IPEI. Meanwhile, in the short term, changes in HDI and economic growth can affect IPEI up to five periods ahead. These findings provide crucial insights for the formulation of inclusive economic development policies in the region.